Exploring the Antimicrobial and Immunomodulatory Potential of Gecko-Derived Cathelicidin Gj-CATH5 - Shasha Cai; Ningyang Gao; Junhan Wang; Jing Li (Biomolecules)
Regulating the innate immune response against infections, particularly drug-resistant bacteria, is a key focus in anti-infection therapy. Cathelicidins, found in vertebrates, are crucial for pathogen resistance. Few studies have explored gecko cathelicidins’ anti-infection properties. Recently, five new cathelicidins (Gj-CATH1-5) were identified in Gekko japonicus. The peptide Gj-CATH5, from G. japonicus, shows promise against Pseudomonas aeruginosa through various mechanisms. This study examined Gj-CATH5’s protective effects using in vitro and in vivo models, finding that it significantly reduced bacterial load in a mouse infection model when administered before or shortly after infection. Flow cytometry and the plate counting method showed that Gj-CATH5 boosts neutrophil and macrophage activity, enhancing chemotaxis, phagocytosis, and bactericidal functions. Gj-CATH5 increases ROS production, MPO activity, and NET formation, aiding pathogen clearance. Its amphipathic α-helical structure supports broad-spectrum bactericidal activity (MBC: 4–8 μg/mL) against Gram-negative and antibiotic-resistant bacteria. Gj-CATH5 is minimally cytotoxic (<8% hemolysis at 200 μg/mL) and preserves cell viability at therapeutic levels. These results highlight Gj-CATH5’s dual role in pathogen elimination and immune modulation, offering a promising approach to combat multidrug-resistant infections while reducing inflammation. This study enhances the understanding of reptilian cathelicidins and lays the groundwork for peptide-based immune therapies against difficult bacterial infections.